2013
DOI: 10.1002/jrs.4197
|View full text |Cite
|
Sign up to set email alerts
|

Switching of hydrogen bonds of water in ionic liquid, 1‐butyl‐3‐methylimidazolium tetrafluoroborate

Abstract: We have investigated temperature‐induced Raman spectral changes of deuterated water in an ionic liquid, 1‐butyl‐3‐methylimidazolium tetrafluoroborate ([bmim][BF4]), between room temperature and 77 K. The comparison of the OH and OD stretching vibrational spectra at 77 K shows that the strength of the hydrogen bonds in [bmim][BF4]–water mixtures strongly depends on the type of water, i.e. H2O and D2O. In the [bmim][BF4]–D2O system, remarkably strong hydrogen bonds form at low temperatures, but they switch to ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Previous studies have shown water will primarily hydrogen bond with anions rather than cations. 51,52,59 The calculated RDFs and SDFs indicate that water resides close to the anions near hydrogen bonding acceptor atoms. Hydrogen bonding occupancy between anions and water was therefore calculated by normalizing the number of water molecules to allow a direct comparison of anions.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown water will primarily hydrogen bond with anions rather than cations. 51,52,59 The calculated RDFs and SDFs indicate that water resides close to the anions near hydrogen bonding acceptor atoms. Hydrogen bonding occupancy between anions and water was therefore calculated by normalizing the number of water molecules to allow a direct comparison of anions.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The polar nature of ILs causes strong interactions between ions and water. Previous work has shown that hydrogen bonds are important descriptors for characterizing the structure of both pure ILs and IL/water mixtures. ,, The energetic and geometric criteria used to describe a hydrogen bond can vary significantly in the literature. ,,, In this work, a geometric criterion shown in Figure was used to define hydrogen bonds. , …”
Section: Computational Detailsmentioning
confidence: 99%
“…Based on the above experimental results, a mechanism for superadhesion and self-healing is illustrated schematically in Figure . The bridging effect of BF 4 – formed strong interactions between the imidazolium cation on the backbone and −OH on the substrates through ionic and hydrogen bonds. , In addition, the compatibility between PIL and IL allows the flexible motion of polymeric chains, validated by the low T g from DSC (Figure S11), thus facilitating interface wetting and resulting in the IG sheet being successfully anchored on the substrates. According to different interfaces, the hydrophobic group (butyl group) and hydrophilic group (imidazole ring) in the IG also played certain roles in interfacial bonding.…”
Section: Resultsmentioning
confidence: 99%
“…Three different water populations can be identified as network water (NW), multimer water (MW), and intermediate water (IW). They manifest as subpeaks at 2280–2380, 2550–2700, and 2400–2540 cm –1 , respectively. The NW molecules are organized in a tetrahedrally ordered hydrogen-bonding network to form an icelike structure, whereas the non-H-bonded or weakly H-bonded water molecules are designated as MW. The IW molecules are involved in a distorted hydrogen-bonding network with neighboring molecules other than water.…”
Section: Results and Discussionmentioning
confidence: 99%